VD_FINDINFO Jug / 2025 / 107 vom 12. November 2024 - VD Tribunal cantonal (2024)
ADMISSION DE LA DEMANDE, REFORMATIO IN PEJUS, PRINCIPE DE L'ACCUSATION | 93 al. 2 let. a LCR, 97 LCR, 391 CPP (CH), 9 CPP (CH)